Integrated Vehicle Service Platform based on Ontology Learning for Connected Car - Ryu, Minwoo; Cha, Si-Ho (International Journal of Engineering and Technology, 2019)
The recent efforts in academia and industry represent a paradigm shift that allow to emerge connected car. Furthermore, the fifth-generation (5G) technology accelerates realization of the connected car era. In the connected car services, the 5G enables to provide high-speed communication between vehicles to change information. In particular, they can exchange bulk data in very short period using the technology. Accordingly, connected car services would provide intelligent services. For example, they can provide self-driving service without human control. Here, the vehicles would exchange data collected from their environments to determine driving path or controlling. Furthermore, they can control diverse devices such as home appliances according to requirement of drivers. To support the services, connected car services consists of four typeâ€™s service categories corresponding to their support types: vehicle to vehicle (V2V); vehicle to infrastructure (V2I); vehicle to pedestrian (V2P) and vehicle to network (V2N). In other to provide more intelligent connected car services in each service category, we propose a novel service platform named for an integrated vehicle service platform (IVSP) to integrate existing connected car services. To this end, we develop an ontology-based service repository to save and register vehicle services. We also develop a web-based service composition tool. To show the feasibility of IVSP, we develop a prototype service for intelligent vehicle service (i.e., home appliances controlling) using IVSP. We expect that our proposed platform could eventually contribute to providing people in connected car services.Â Â